Manifestation of cocoa commodity issues: a pragmatic analysis of a comparison of newspaper headlines between Malaysia and Indonesia - Syarifuddin, Noviatin; Abu Samah, Asnarulkhadi; Sufian Burhan, Nik Ahmad; Arif Shah, Jasmin (NeuroQuantology, 2022)
World Bank (2020) show a total of 570 million agro-commodity farms are managed by smallholder communities across the globe. The involvement of smallholder communities in the field of cocoa ventures in terms of productivity issues, challenges and constraints through pragmatic analysis of newspaper headlines to preserve cocoa commodities is very poorly explored. Meanwhile, the mass media through the role of the press in channeling information on agricultural development education is very significant to the smallholder community. Thus, this study aims to analyze a pragmatic comparison of the presentation of cocoa commodity issues through the type of speech act in newspaper headlines in Malaysia and Indonesia. Quantitative and qualitative research approach through content analysis were used to analyze the theme of cocoa commodities in selected newspaper headlines in Malaysia and Indonesia. Data related to cocoa commodity issues were gathered randomly covering 50 data from the Malaysian newspaper and 75 data from Indonesian newspaper. Newspaper headline data from 2017 to 2021 were analyzed using thematic analysis techniques through the framework of Speech Act Theory (Searle 1969). The results of the study found that a total of five types of speech act are often used in newspaper headlines related to cocoa commodities in Malaysia and Indonesia. The findings of the study in Malaysia showed that the type of assertive speech act (48.0%) was dominant compared to the type of speech act that is directive (10.0%), commissive (22.0%) and declarative (20.0%). Meanwhile, in Indonesia, the findings found that the type of assertive speech act (48.0%) was dominant compared to the type of speech act that is directive (13.3%), commissive (16.0%), expressive (10.7%) and directive (12.0%). Clearly, comparative study between the two countries shows that the type of assertive speech act is more dominant in the manifestation of cocoa commodity issues. It is in line with the function of the press to report on the development of the country's agricultural sector.